2012
DOI: 10.1016/j.biomaterials.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell type-specific responses to glycomimetic functionalized collagen

Abstract: Despite their noted functional role, glycans have had limited therapeutic use due to difficulties in synthesis and quick degradation in vivo. The recent discovery of glycomimetics has provided new opportunities for their application. In this study, we have functionalized type I collagen with peptide mimics of two glycans: (1) polysialic acid (PSA) and (2) an epitope first discovered on human natural killer cells (HNK-1). These glycans and their glycomimetic counterparts have been shown to be important regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
1
24
1
Order By: Relevance
“…In its hydrogel form, collagen provides a highly controlled environment for nerve cells to grow by providing both mechanical and biological support for neuritogenesis [26]. In a previous study, we confirmed the in vitro bioactivity of type I collagen hydrogels that were functionalized with PSA and HNK-1 glycomimetics and showed that the molecules retain their modality specific responses towards neural cells after conjugation [27]. …”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…In its hydrogel form, collagen provides a highly controlled environment for nerve cells to grow by providing both mechanical and biological support for neuritogenesis [26]. In a previous study, we confirmed the in vitro bioactivity of type I collagen hydrogels that were functionalized with PSA and HNK-1 glycomimetics and showed that the molecules retain their modality specific responses towards neural cells after conjugation [27]. …”
Section: Introductionmentioning
confidence: 60%
“…This has been attributed to a number of reasons including the local inflammatory response, ingrowth of fibrous scar tissue, lack of mechanical support for emerging neurites, and more recently the malrouted regrowth of axons. We have previously shown that covalent conjugation of glycomimetic HNK-1 and PSA peptides to type I collagen results in neural cell type-specific responses in vitro [27]. Given these unique, modality-defined effects, we investigated the potential for glycomimetic functionalized collagen to promote axonal regeneration and targeting in a challenging, 5 mm gap size femoral nerve injury model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound has been implicated in preferential motor reinnervation, as well as axon path finding in regenerating peripheral neurons (67). Glycans are complex to synthesize and have a short half-life in vivo , making them minimally useful for in vivo applications (68). Glycan mimetics, however, have a great potential for achieving the same effect without these complications (69).…”
Section: Small Molecule Mediated Peripheral Nervous Regenerationmentioning
confidence: 99%
“…Sterile PBS or type I collagen hydrogel was used as luminal fillers. Type I collagen hydrogels (2.0 mg/mL) were prepared as previously described . Both PE tubes and SA‐NGCs were incubated with type I collagen hydrogel fillers at 37°C to ensure hydrogel self‐assembly.…”
Section: Methodsmentioning
confidence: 99%